Studi pengaruh variabel proses dan kinetika ekstraksi nikel dari bijih nikel laterit menggunakan larutan asam sulfat pada tekanan atmosferik - Wahab; Erwin Anshari; Marwan Zam Mili; WD. Rizky Awaliah Nafiu; Muh. Nuzul Khaq; Deniyatno; Firdaus; Yayat Iman Supriyatna (Jurnal Rekayasa Proses, 2021)
Leaching at atmospheric pressure is one of the leaching methods of concern because it has several advantages, namely that it can process low-level nickel ore, can operate at temperatures >100 ⁰C at atmospheric pressure, and can be used in saprolite and limonite ores. In this research, nickel extraction from nickel laterite ore was carried out using sulfuric acid solution (H2SO4) as a leaching agent. The variables that were varied in the leaching process were temperature (30, 60, and 90 ⁰C), sulfuric acid concentration (0.2, 0.5, and 0.8 molar) and leaching time (30, 60, and 90 minutes). In this study, a 3-factor analysis of variance (ANOVA) was used to see the significance of the variable effects and the order of the most influential variables. In addition, leaching kinetics was studied by shrinking core models to determine rate determining step. The results showed that the increase in temperature, sulfuric acid and leaching time produced a higher percentage of extracted nickel. Based on the 3-factor ANOVA, the order of the most influential variables was obtained, namely temperature, acid concentration and leaching time. The kinetics analysis showed that rate determining step of leaching ore nickel laterite with H2SO4 solution on atmospheric pressure is controlled by diffusion through solid layer product.